Influence of gamma and electron radiation on perfluorinated optical fiber material composition - Leal-Junior, Arnaldo Gomes; Theodosiou, Antreas; Frizera-Neto, Anselmo; Fernandes, António José S.; Stancalie, Andrei; Ioannou, Andreas; Mihalcea, Razvan; Negut, Daniel Constantin; Ighigeanu, Daniel I.; Kalli, Kyriacos; Marques, Carlos Alberto F. (My University, 2023)
This letter presents a material analysis of the cyclic transparent optical polymer (CYTOP) fiber when exposed to gamma and electron radiation. In this case, the influence of the radiations in the CYTOP material composition is analyzed using the FTIR and Raman spectroscopy, where the latter is applied on two regions of the optical fiber, the core and overcladding. Furthermore, a CYTOP fiber without been exposed to radiation is also tested. Results show that the electron radiation leads to 60% higher variation in the material composition when compared with the gamma radiation in FTIR tests. The Raman spectroscopy indicates that both radiation conditions lead to compositional changes in the CYTOP fiber core, where peaks related − CH3 and aromatic C − H bonds appeared in these conditions. Such effect is not only related to molecular rearrangement, but also thermal effects when the fibers are subjected to gamma and electron radiations.
Keywords: Electron radiation; Gamma radiation; Optical materials; Polymer optical fibers